Fluency and its teaching - Guillot, Marie-Noëlle, 1955- (Modern languages in practice ;, 1999)
"We can all recognise fluency, but cannot quite put our finger on its constituents. We can all practise to be fluent, but do not understand what linguistic and paralinguistic operations are involved, and therefore cannot teach others, or ourselves, to be fluent. This book tries to solve this puzzle. It is both an enquiry into fluency, and an argument for doing it pedagogical justice. It begins by exploring perceptions and accounts of fluency, both popular and professional, to understand their common denominators. It goes on to pinpoint, by analysis of various kinds of discourse, the specific features which promote fluency, in production and reception, while emphasising its relative, interactional and fluctuating nature in practice."--Jacket